The global health dimensions of asbestos and asbestos-related diseases - Ramazzini, Collegium (La Medicina del Lavoro, 2016)
The Collegium Ramazzini (CR) reaffirms its long-standing position that responsible public health action is to ban all extraction and use of asbestos, including chrysotile. This current statement updates earlier statements by the CR with a focus on global health dimensions of asbestos and asbestos-related diseases (ARDs). The ARD epidemic will likely not peak for at least a decade in most industrialized countries and for several decades in industrializing countries. Asbestos and ARDs will continue to present challenges in the arena of occupational medicine and public health as well as in clinical research and practice, and have thus emerged as a global health issue. Industrialized countries that have already gone through the transition to an asbestos ban have learned lessons and acquired know-how and capacity that could be of great value if deployed in industrializing countries embarking on the transition. The accumulated wealth of experience and technologies in industrialized countries should thus be shared internationally through global campaigns to eliminate ARDs.